Manajemen Kesiswaan Dalam Meningkatkan Prestasi Non Akademik Siswa Di Sekolah Menengah Kejuruan Negeri 8 Jember - Silfiyaningsih, Mela (YPI Ulul Albab, 2024)
Student management is an activity that is planned and carried out deliberately, and continuous coaching is carried out so that students can follow the activity process effectively and efficiently. Because in the world of education, achievement is often a measure of an institution's success. In efforts to improve non-academic achievements, problems often occur because not all educational institutions provide permission, therefore there is a need for good student management and ongoing support. Meanwhile, data collection techniques were obtained through observation, interviews and documentation. Meanwhile, data analysis uses theories from Milles and Huberman, namely data condensation, data presentation and drawing conclusions. Validity of data using triangulation techniques and sources. The results of this research are that planning student activities at SMKN 8 Jember begins with identifying academic activities that are tailored to the talents and interests of students, socializing non-academic activities for students, identifying supporting infrastructure needed for non-academic activities, implementing which carried out by SMKN 8 Jember, namely at the beginning by organizing non-academic activities, participating students in academic activities, grouping students, appointing supervisor teachers, scheduling extracurricular activities, controlling student training discipline, evaluating activities at SMKN 8 Jember at the beginning and end, which includes activities comparison of non-academic achievement goals or hopes that will be realized, searching for the causes of whether or not the specified targets are met.